PERAN KELOMPOK PEREMPUAN DALAM PENGELOLAAN DESA WISATA SAMIRAN, SELO, BOYOLALI - , DAYANG NEVIA AFRIANS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research has three aspect of analyist (1) The management of Desa Wisata Samiran/DWS (2) The role of women group in DWS (3) The influence factors in the role of DWS women group. The goals of this study are how to describe the past and the future concept of DWS management to maximal the role of women group for the increased number of tourist. This research use descriptive of qualitative method with the prime data (interview, observation and questionnaire) and seconder data (literature) for data collection. The sample of this research make use of group focusing because the number of group member too small (8 â 15 person/group) and the number of group who participate in DWS are four groups only. There are 12 women as the respondens with differently degrees of citizen participation that describe how important of self skill training and factors that influence their roles in DWS management. The research outcome shows (1) at the George R. Terry Sixâs M, DWS has four resources only. They are Men, Methods, Money and Markets. Machines and Materials are not detected, because DWS manages services (2) The factors that influence role of women group in DWS management are tough worker type, self skill needs, self actualization needs and economic factor. Training for self skill upgrading has make increase quality of tourist services, new product creating and income that come from women group (4) in the number of society member who involved DWS, 35% are women and 65% are men. But in the number of DWS income who come from member of group, 66% are women group, 35% are men group (the women group more productive than men group). Key words: Training and Management